A Review on The Microstructure of Interfaces in Reinforced Concrete and Its Effect on The Bond Strength - Muslim, Fadhilah (CSID Journal of Infrastructure Development, 2020)
Studies on the microstructural characteristics of the interfaces in reinforced concrete and its effect on the mechanical properties i.e. bond strength have been conducted for many years, even since 1956. However, a summary of existing knowledge and findings related to the different types of interfaces is still lacking. Therefore, this paper reviews the characteristic of different types of interfaces in reinforced concrete including those between: a) aggregate particles and cement paste, i.e. the interfacial transition zone (ITZ); b) steel reinforcing bars and concrete; and c) old (substrate) and new concrete (repair materials). The aim of this review is to show how similar and different the characteristics of interfaces in reinforced concrete. Such information is important for understanding the properties and durability as well as how it might affect the long-term performance of concrete structures.